(untitled) (Ibrahim Cardiac Medical Journal, 2023)
Background & objective: The development of nosocomial pneumonia represents an imbalance between normal host defenses and the ability of microorganisms to colonize and then invade the lower respiratory tract. Although some common bacteria are involved in nosocomial infection, bacteriological profile differs from geographical location and setting of the hospital. The present study was therefore, carried out to identify the common causative organisms of nosocomial pneumonia and determine their antibiotic sensitivity in BIRDEM General Hospital, Dhaka, Bangladesh. Methods: This cross-sectional study was conducted in Intensive Care Unit (ICU), BIRDEM General Hospital, Dhaka, Bangladesh. A total of 110 subjects with nosocomial pneumonia admitted in the ICU over a period of six months from January 2021 to June 2021 were consecutively included in the study. Samples included (blood, urine, sputum/tracheal aspirate wound swab etc.) were cultured in standard media for isolation of potential pathogens. From 110 subjects 110 samples were collected. Isolates were identified by standard FAN method. For each isolate antibiotic susceptibility was performed by Kirby Bauer disk diffusion technique. Isolates with intermediate susceptibility were considered resistant. Result: The mean age of the sampled population was 55.6 ±13.6 (range:38-65) years. Among 110 study subjects, 68(61.8%) were male and 42 (38.2%) were female in the study population. Patients with nosocomial pneumonia were presented with raised temperature (100%), leukocytosis (86.3%), tachycardia (82.7%) and tachypnoea (70.9%). Out of 110 samples, microorganisms were isolated from 102 samples (92.9%). Growth revealed Pseudomonas (28.4%), Acinetobacter (42.1%), Staphylococcus aureus (3.9%), Enterococcus (4.9%), E. coli (6.7%), Klebsiella (5.9%), Enterobacter (3.9%), Citrobacter (1.9%) and Candida sp. (1.9%). From culture sensitivity test, it was found that majority (90%) of the isolated organisms were resistant to Quinolones and 3rd generation cephalosporin. Majority of the E coli and Klebsiella were less resistant (9.6% and 14.3%) to Imipenem. Colistin resistance was less than 50%. Piperacillin and Tazobactam combination showed less than 50% resistance in case of Acinetobacter and Klebsiella. Conclusion: The study concluded that as patients with nosocomial pneumonia admitted in ICU are already ill, it would be unwise to wait for result of antibiotic sensitivity test and it is recommended that Colistin or Imipenem or Piperacillin and Tazobactam combination should be stared to save the life of the patients and then start suitable antibiotic after obtaining culture –sensitivity result. Ibrahim Card Med J 2022; 12 (1): 35-39